PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI BERBASIS CANVA PADA PEMBELAJARAN IPAS KELAS 3 SDN GAYAM 1 - Veni Aulia Pratamaputri (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to develop Canva-based animated instructional videos for the Natural and Social Sciences (IPAS) subject for third-grade students at SDN Gayam 1, and to determine their feasibility and effectiveness in enhancing student interest and learning outcomes. The study employs the Research and Development (RD) method using the 4D model, comprising the Define, Design, Develop, and Disseminate stages. The research subjects were third-grade students at SDN Gayam 1. Data collection techniques included observation, interviews, validation sheets, learning outcome tests, and questionnaires. The results indicate that the Canva-based animated instructional videos are valid, practical, and effective for use in IPAS instruction. The use of this medium increased student engagement in the learning process and facilitated a better understanding of the material regarding the growth of living things